Barriers and facilitators to HIV and syphilis rapid diagnostic testing in antenatal care settings in low-income and middle-income countries: a systematic review. Issue 11 (1st November 2022) - Zhang, Ye; Guy, Rebecca; Camara, Hawa; Applegate, Tanya L; Wiseman, Virginia; Treloar, Carla; Lafferty, Lise
Abstract : Background: Testing and treatment during pregnancy is a well-established and cost-effective prevention strategy, which relies largely on use of rapid diagnostic tests (RDTs). Yet, in many low-income and-middle-income countries, the uptake of RDTs is suboptimal. A qualitative meta-synthesis was conducted to identify the barriers and enablers to use of HIV and syphilis RDTs among pregnant women in low-income and middle-income countries. Methods: This review was conducted using PRISMA guidelines. Eligible studies included peer-reviewed publications, which used qualitative methods to explore HIV and syphilis RDT in antenatal care clinics in low-income and middle-income countries. Studies focusing on perspectives of pregnant women, healthcare workers and/or stakeholders were included. We used an inductive approach informed by a modified socioecological model to synthesise the data. Results: 62 manuscripts met the eligibility criteria. For pregnant women, initial acceptance of the RDT and continuation in antenatal care depends on the perception that engaging in testing will be a beneficial experience for their baby and themselves, often influenced by the provision of services that are gender-sensitive, confidential, respectful, flexible and considers their well-being into the future. Local sociocultural beliefs about pregnancy and diseases, awareness of diseases and gender roles in society also influenced RDT acceptability among pregnant women. For healthcare workers, the ability to provide high-quality RDT care required ongoing training, accurate and easy to use tests, support from supervisors and communities, sufficient resources and staffing to provide services, and reliable salary. At the stakeholder level, well-developed guidelines and health system infrastructures were imperative to the delivery of RDT in antenatal clinics. Conclusion: Our findings highlight clear gaps to the provision of sustainable and culturally acceptable maternal HIV and/or syphilis screening using RDTs. In addition, greater attention needs to be paid to community stakeholders in promoting the uptake of RDT in antenatal clinics. PROSPERO registration number: CRD42018112190.